(untitled) (International Journal of Engineering and Computer Science, 2017)
Recently, security of real-time systems becomes a very important concern in real-time database systems (RTDBS). However, security is becoming a more significant challenge in several real-time applications. Nowadays, there are many multilevel security (MLS) models which can make RTDBS more secure. Three information security models based on multilevel security policy have been discussed, analyzed and compared in this paper. Moreover, this paper concludes that BLP model focuses only on the confidentiality of information and ignores the integrity. On the other hand, Biba and Clark-Wilson models protect the integrity only.